Oceans of Consolation : Personal Accounts of Irish Migration to Australia - Fitzpatrick, David (Cornell University Press, 2019)
"An ocean of consolation" was what one young Irish emigrant in rural Australia called a letter from his father in County Clare in 1855. Similar strength of feeling is often found in the intriguing letters that David Fitzpatrick has unearthed for this extraordinary collection. Oceans of Consolation offers historians and family researchers novel and sophisticated ways of reading old letters. It opens to us the daily preoccupations of ordinary women and men with little education and fewer material possessions, as they try to overcome the separation from family and friends created by emigration. Fitzpatrick includes the personal correspondence of fourteen families of Irish emigrants in the Australian colonies, giving equal attention to letters to and from Australia. He reproduces in full more than one hundred letters dating from 1843 to 1906, and includes a generous selection of contemporary engravings and photographs. Fitzpatrick's detailed commentaries offer biographical narratives for all of these emigrants, tracing their Irish backgrounds and Australian careers. Parting company with editors of comparable collections, he pays special attention to the words and idiom by which letterwriters expressed their everyday concerns and sought or offered reassurance and advice. He believes that personal letters provide not only unique evidence of the hopes and fears of emigrants but also an important avenue for exploring popular Irish culture.